2020
DOI: 10.1038/s41598-020-62759-5
|View full text |Cite
|
Sign up to set email alerts
|

First comprehensive TSC1/TSC2 mutational analysis in Mexican patients with Tuberous Sclerosis Complex reveals numerous novel pathogenic variants

Abstract: echavarría 4 , carlos G. todd-Quiñones 5,6 & Ariadna González-del Angel 1* the aim of this study was to improve knowledge of the mutational spectrum causing tuberous sclerosis complex (tSc) in a sample of Mexican patients, given the limited information available regarding this disease in Mexico and Latin America. Four different molecular techniques were implemented to identify from single nucleotide variants to large rearrangements in the TSC1 and TSC2 genes of 66 unrelated Mexican-descent patients that clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
1
14
0
2
Order By: Relevance
“…The findings from this study also corroborate with these previous studies, indicating a significant majority of TSC patients with a mutation at the TSC2 genetic locus, with a TSC1 : TSC2 mutation ratio of 2.8 TSC2 patients for every TSC1 patient, or TSC1 and TSC2 mutation rates amongst the cohort at 25% and 72%, respectively. Furthermore, the detection rate of TSC mutations was determined as 97%, superseding previous studies where the detection rate ranged from 82 to 94% [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study also corroborate with these previous studies, indicating a significant majority of TSC patients with a mutation at the TSC2 genetic locus, with a TSC1 : TSC2 mutation ratio of 2.8 TSC2 patients for every TSC1 patient, or TSC1 and TSC2 mutation rates amongst the cohort at 25% and 72%, respectively. Furthermore, the detection rate of TSC mutations was determined as 97%, superseding previous studies where the detection rate ranged from 82 to 94% [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…LOF pathogenic variants in the TSC1 gene leading to TSC1/hamartin haploinsufficiency have previously been associated with the juvenile-onset lysosomal storage disease TSC (12,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…7 ). LOF pathogenic variants in the TSC1 gene leading to TSC1/hamartin haploinsuffíciency have previously been associated with the juvenile-onset lysosomal storage disease TSC ( 12, 51, 52 ). In earlier clinical-translational studies, we have shown a linkage between TSC1 gene and age-related tauopathies ( 11, 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Συγκεκριμένα, δεδομένα από πολλές μελέτες αναφέρουν ότι η συχνότητα ανεύρεσης μετάλλαξης του TSC2 γονιδίου κυμαίνεται μεταξύ 46-85% και του TSC1 μεταξύ 12-33%. [40][41][42][43]54,[58][59][60][61][62][63][64][65][66][67][68][69] Παρόμοια ποσοστά προέκυψαν κι από τον γονιδιακό έλεγχο 902 ασθενών της βάσης δεδομένων TOSCA, όπου το 63.3% των ασθενών έφερε μετάλλαξη στο TSC2 γονίδιο και το 19.7% των ασθενών στο TSC1 γονίδιο. 44 Ειδικότερα στον ελλαδικό χώρο, σε δύο πρόσφατες μελέτες του 2018 και 2017, η συχνότητα μετάλλαξης του ΤSC2 γονιδίου ήταν μεταξύ 53-75% και του TSC1 25-47%.…”
Section: αιτιοπαθογενεια -γενετικηunclassified
“…41,42,65,72 Τα τελευταία χρόνια η χρήση περισσότερο ευαίσθητων μεθόδων όπως το NGS, η MLPA και πρόσφατα η μέθοδος MPS οδήγησε στην ανίχνευση νέων ΠΜ μειώνοντας το ποσοστό μη ανιχνεύσιμων ΠΜ <10%. 64,69,70,73 PRR5/Protor). [108][109][110] Σε αντίθεση με το μονοπάτι του mTORC1, το σηματοδοτικό μονοπάτι του mTORC2 δεν έχει πλήρως καθορισθεί.…”
Section: αιτιοπαθογενεια -γενετικηunclassified